Deep immunophenotyping of circulating immune cells in major depressive disorder patients reveals immune correlates of clinical course and treatment response - Fabiola Stolfi; Claudio Brasso; Davide Raineri; Virginia Landra; Camilla Barbero Mazzucca; Ali Ghazanfar; Lorenza Scotti; Riccardo Sinella; Vincenzo Villari; Giuseppe Cappellano; Paola Rocca; Annalisa Chiocchetti (Brain, Behavior, & Immunity - Health)
Major Depressive Disorder (MDD) is a widespread psychiatric condition impacting social and occupational functioning, making it a leading cause of disability. The diagnosis of MDD remains clinical, based on the Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 criteria, as biomarkers have not yet been validated for diagnostic purposes or as predictors of treatment response. Traditional treatment strategies often follow a one-size-fits-all approach obtaining suboptimal outcomes for many patients who fail to experience response or recovery. Several studies have reported an association between MDD and immune system dysregulation, but few have focused on the deep characterization of circulating cells, during the acute phase of MDD. This work aimed at immunophenotyping peripheral blood cells in the relapse phase of the disorder, to identify relevant cell populations for clinical monitoring of patients. Multiparametric analysis was performed on the peripheral blood of 60 MDD patients using flow cytometry to identify lymphocytes (naïve/effector, memory, regulatory) and myeloid cells (dendritic cells, monocytes). We studied the associations between immunophenotype and depressive symptoms, social and working functioning, and subjective quality of life during the acute phase and after three months of treatment. Multivariate analysis showed that CD4+ terminally differentiated effector memory (TEMRA) were associated with more depressive symptoms with a particular emphasis on anhedonic features and worse social and working functioning and quality of life. CD8+ TEMRA were associated with those depressive symptoms related to hopelessness. Conversely, ICOS + Tregs were associated with low-intensity suicidal ideation, suggestive of a protective role. Baseline T CD4+ effector memory (EM) was a negative predictor of reduction of depressive symptoms after three months of treatment, whilst plasmacytoid dendritic cells (pDC) were predicting reduction of hopelessness. These results confirm the involvement of the immune system in MDD and demonstrate the existence of immunological signatures associated with the severity of major depressive episodes and treatment response that could guide clinical monitoring and future personalized therapies.